Sotho/Tswana stone-wall settlements : investigating the nature of aggregation and variability in late iron age settlements in the Vredefort Dome : a geographic information systems application - Nkhasi, Mamakomoreng Exinia (Department of Archaeology, 2014)
The Vredefort Dome is a meteorite impact site (S26°51'36", E27°15'36") approximately 120km south-west of Johannesburg and about 300km north-east of Bloemfontein. It is one of South Africa's eight World Heritage Sites and straddles both North West and Free State provinces. Apart from its remarkable geology, the Vredefort Dome also has great faunal and floral biodiversity, as well as a wealth of cultural heritage. The Late Iron Age stone-walled settlements built by Sothoffswana speakers form part of this rich cultural heritage, and it is these that are under investigation in this study. Previous archaeological survey and research has shown that Sotho/Tswana speaking peoples densely populated this area during Late Iron Age (from 1400 -1800 AD). While settlement survey has identified three stone-wall settlement types (Group I, Group II and Group III) in the Vredefort Dome, this previous survey had been limited in extent. This research used aerial photographs to survey the whole Vredefort Dome and thereby expanded the sample. This research has focused mainly on the two dominant settlement types, namely Group I and Group II. This work has allowed a more detailed description of settlement preferences and an understanding of site location in relation to biophysical factors such as geology, topography and veld types. Additionally, it has been possible to identify relatively discrete clusters of settlements and through the use of Geographic Information Systems (GIS), homesteads and cattle enclosures have been mapped and measured. The extent of homestead aggregation has also been measured and with this data, comparisons between settlements within clusters have been assessed in relation to possible political and social hierarchies. It is concluded that among Group I settlements and using some appropriate ethnography, there is no obvious settlement hierarchy. In the case of Group II settlement, larger aggregations represent the defensive response to the conditions of the early 19th century difaqane. While these must be underpinned by more centralised political control, on the basis of cattle enclosure and homestead sizes, central authority is not obvious. In contrast, these aggregations are briefly compared with the large Western Tswana towns, where political centralisation can be more easily identified. This research is organized in five chapters: Chapter one introduces the background literature review which has influenced my research interest, and outlines the methodology followed in obtaining relevant data. The outline and discussions of the results are represented in chapter two, exploring is the distribution of different stone-walled sites within the ecological and biophysical context. Chapters three and four closely examine the distribution and locality of specific stone-wall settlement patterns, Group I and Group II respectively. And lastly chapter five represents the concluding discussion.